Seasonal marine litter abundances and accumulation rates on 24 beaches of 8 Mediterranean islands (2017-2019) - Michaël Grelaud; Patrizia Ziveri (PANGAEA, 2020)
The Mediterranean Sea and its coastal systems are threatened by intense anthropogenic pressures including rapid accumulation of marine litter by diverse human activities. The region, which is the world extquotesingles leading touristic destination, has to face a seasonal increase of waste generation due to the seasonal influx of visitors. The beaches, extremely crowded during the summer, are particularly vulnerable since they are proven to be concentrated accumulation zones and one of the main gateways of litter to enter the marine system. We found that the accumulation rates of marine litter on Mediterranean island beaches follow a seasonal pattern, increasing up to 4.7 times during the high season, representing a daily load of 40.6 10? ± 11.5 10? items/day extrapolated to all the islands of the region. We developed an accumulation index to assess the dynamics of marine litter and support efficient mitigation strategies by local authorities. To limit marine litter production attributable to recreational activities, a series of pilot actions implemented during the high touristic season, demonstrated a substantial reduction (up to 52.5%). The implementation towards an efficient and sustainable tourism business model is urgently required.